Perancangan Feed Instagram Portofolio Brand Ratulangi Sebagai Media Promosi Kawakibi Digital Branding (International Forum of Researchers and Lecturers, 2024)
The design of Instagram feed as a promotional media for Ratulangi brand portfolio is part of Kawakibi Digital Branding marketing strategy. The design process is carried out through briefing, brainstorming, execution, assistance, revision, and collection stages. The result is the design of the Ratulangi Natural Skincare brand portfolio for Kawakibi's Instagram social media content. These stages involved research, design execution, and assistance to ensure the final result met the expectations of Kawakibi Digital Branding partners. These stages emphasize the importance of a design process that involves multiple stages to achieve a satisfactory end result for the client, as well as highlighting the strategic role of social media in marketing.